2018
DOI: 10.2147/opth.s161217
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors in the treatment of streptococcal endophthalmitis

Abstract: ObjectiveTo evaluate visual outcomes and possible predictive factors in the treatment of infectious endophthalmitis caused by Streptococcus species during 2012–2016 at a large referral eye center in northeastern Thailand.MethodsA retrospective medical record chart review of patients with culture-positive endophthalmitis caused by Streptococcus species was conducted. Demographic data including age, gender, occupation, duration of symptoms, time to surgery, surgical procedures, initial visual acuity at presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…According to our data analysis, there was a relationship between different therapy and vision improvement. According to figure 1 and table 4, in addition to enucleation, the improvement of visual acuity was statistically significant by various treatment methods, and in the PPV group was significantly higher than that in other groups, which was similar to the results of other researches [4,6]. Therefore, PPV is the main therapy strategies in infectious endophthalmitis [4,5,22].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to our data analysis, there was a relationship between different therapy and vision improvement. According to figure 1 and table 4, in addition to enucleation, the improvement of visual acuity was statistically significant by various treatment methods, and in the PPV group was significantly higher than that in other groups, which was similar to the results of other researches [4,6]. Therefore, PPV is the main therapy strategies in infectious endophthalmitis [4,5,22].…”
Section: Discussionsupporting
confidence: 75%
“…Streptococci can produce severe endophthalmitis with a poor visual outcome, whereas coagulasenegative staphylococci cause milder endophthalmitis in general [5]. Yosanan et al found that the only possible predictive factor associated with improved visual outcomes was PPV within 3 days [6].…”
Section: Introductionmentioning
confidence: 99%
“…These shifting trends suggested that age may influence the microbiological spectrum of endophthalmitis. Previous studies demonstrated that streptococcal infection was associated with poor vision outcome in endophthalmitis [36][37][38]; therefore, a higher proportion of streptococcal infections in children, especially in younger children, merits clinical attention. Antibiotic resistance is a topic of concern worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were classified as having "improved" VA when their best-corrected VA (BCVA) rates were better post-therapy than pre-therapy. They were classified as "not improved" when the final BCVA rates were stable or worse than the initial values [6].…”
Section: Measurementsmentioning
confidence: 99%
“…Durand reported that there was a reasonably high correlation between the visual outcome and pathogenic microbiology [5], Streptococci can produce severe endophthalmitis with a poor visual outcome, whereas coagulase-negative staphylococci cause milder endophthalmitis in general. Yosanan et al found that the only possible predictive factor associated with improved visual outcomes was pars plana vitrectomy (PPV) within 3 days [6].…”
Section: Introductionmentioning
confidence: 99%